TAX AVOIDANCE: BERKAIT DENGAN DERIVATIF KEUANGAN SERTA FIXED ASSET INTENSITY - Airlin Permata Sari; Andrik Gastri Widjatmiko; Yety Anggraini; Wahyu Wismawati (JURNAL ILMIAH EDUNOMIKA, 2025)
This research begins with the concern that the realization of total tax revenue does not meet expectations. This study examines 37 banking companies, comprising a total of 292 firm-year samples, using panel data regression analysis methods. Based on the findings, it can be concluded that the financial derivative variable has a positive influence on tax avoidance. Additionally, the fixed asset intensity variable also has a negative impact on tax avoidance. Ultimately, this research is expected to provide contributions to companies, future researchers, and stakeholders regarding tax avoidance.